Interactive-Based Media and Effective Learning Strategies to Improve Students' Digital Literacy: A Structured Literature Review - Budiarto, Mochamad Kamil; Khotimah, Khusnul; Maulana, Iwan; Andrianto, Rico Eko; Rabbani, Arsyananda

(untitled) - Syahmi, Favian Avila; Amarulloh, Adhitya (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This systematic literature review investigates the effectiveness of interactive media and specific learning strategies, such as project-based learning (PBL) and augmented reality (AR), in improving digital literacy among secondary school students. Analyzing 19 peer-reviewed studies from 2018 to 2024, the review identifies both effective approaches and key barriers. It highlights that while digital tools can enhance students' abilities in content creation, information evaluation, and ethical technology use, their impact depends on well-designed curriculum integration, teacher preparedness, and institutional support. The findings emphasize ongoing challenges, including inadequate infrastructure, insufficient teacher training, and curriculum misalignment, particularly in public schools. In response, the review proposes actionable recommendations to address these barriers, including incorporating culturally responsive media and comprehensive teacher development programs. This study aims to inform policy reforms and provide evidence-based strategies for integrating digital literacy into secondary education, with an emphasis on contextual, interdisciplinary approaches that align with current digital citizenship demands.